Developments allergy in 2019 through the eyes of clinical and experimental allergy, part I mechanisms. Issue 12 (1st December 2020) - Roberts, Graham; Almqvist, C.; Boyle, R.; Crane, J.; Hogan, S. P.; Marsland, B.; Saglani, S.; Woodfolk, J. A.
Abstract: In the first of two linked articles, we describe the development in the mechanisms underlying allergy as described by Clinical & Experimental Allergy and other journals in 2019. Experimental models of allergic disease, basic mechanisms, clinical mechanisms and allergens are all covered.